Sequence types and pleuromutilin susceptibility of Brachyspira hyodysenteriae isolates from Italian pigs with swine dysentery: 2003–2012. Issue 1 (January 2015) - Rugna, G.; Bonilauri, P.; Carra, E.; Bergamini, F.; Luppi, A.; Gherpelli, Y.; Magistrali, C.F.; Nigrelli, A.; Alborali, G.L.; Martelli, P.; La, T.; Hampson, D.J.; et al.
Highlights Isolates of Brachyspira hyodysenteriae recovered from 2003 to 2012 in Italy were analysed. Susceptibility to pleuromutilins (tiamulin and valnemulin) was significantly associated with genetic group. Susceptibility to pleuromutilins (tiamulin and valnemulin) was significantly associated with year of isolation. Isolates in clonal clusters 2 and 7 were more than five times more likely to be sensitive than those in the other clonal clusters.